PRACTICAL USE OF LOGISTIC TOOLS IN PHYSICAL LIFE CYCLE OF DURABLE GOODS - F. D. Vende; V. I. Stepanov; O. V. Rykalina; I. V. Sharova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies logistic functions, processes and procedures accompanying all stages of full physical life cycle of new durable goods. The term ‘new’ means here an original product possessing new values for customers or a product – modification, which in comparison with the basic product has higher productivity, economical and ecological characteristics and possibilities of utilization. Durable goods include technical devices, such as production equipment and transportation means. The full physical life cycle is split into stages and step of their executions. Actually each stage is connected with logistic procedures: opportunity to get new materials and components at the project stage; estimating the number of parts taken from the basic product for the product-modification at the project stage; decision-making concerning out-sourcing and in-sourcing at the pre-production stage; evaluating the stock of material and technical resources at the enterprise at the production stage; expanding the existing distribution channels and searching for new ones at the marketing stage; calculating the need in material resources for warranty service at the operation stage. The article shows also certain lines in developing advance logistics, such reverse logistics, re-cycling logistics and green logistics. These lines van serve as land marks for developers of more economical and ecological technical devices, including transportation means, storage and shop equipment, as well as for developers of low-waste and logistic technologies.